The Effectiveness of Protective Headgear in Attenuating Ball-to-Forehead Impacts in Water Polo - Cecchi, Nicholas J.; Oros, Theophil J.; Monroe, Derek C.; Fote, Gianna M.; Moscoso, Wyatt X.; Hicks, James W.; Reinkensmeyer, David J. (Frontiers in Sports and Active Living, 2019)
Recent reports have demonstrated that there is a serious risk of head impact and injury in water polo. The use of protective headgear in contact sports is a commonly accepted strategy for reducing the risk of head injury, but there are few available protective headgears for use in water polo. Many of those that are available are banned by the sport's governing bodies due to a lack of published data supporting the effectiveness of those headgears in reducing head impact kinematics. To address this gap in knowledge, we launched a water polo ball at the forehead of an anthropomorphic testing device fitted with either a standard water polo headgear or one of two protective headgears. We selected a range of launch speeds representative of those observed across various athlete ages. Mixed-model ANOVAs revealed that, relative to standard headgear, protective headgears reduced peak linear acceleration (by 10.8–21.6%; p < 0.001), and peak rotational acceleration (by 24.5–48.5%; p < 0.001) induced by the simulated ball-to-forehead impacts. We discuss the possibility of using protective headgears in water polo to attenuate head impact kinematics.